Collective creativity and wellbeing dispositions: Children's perceptions of learning through drama. (March 2023) - Stephenson, Lisa
Highlights: Links collective creativity, drama pedagogy, wellbeing and relational learning to change making. Presents a model of Dispositions for Creativity and Wellbeing based on empirical research with children. Presents a pedagogical model of Drama Worldbuilding. Provides new methodological approach to measure relational learning through meta-affect. Provides a heuristic tool for teachers to expand their creative arts repertoire and integrate wellbeing into the curriculum. Expands research on how meaning is made through collective creativity. Abstract: At a time of escalating global climate change and political, educational, social, and economic divides, children face uncertainties about their futures. This is set against a rise in poor wellbeing and mental health amongst children. Whilst global organisations such as OECD Learning Compass 2030 and UNESCO Framework for Action 2030, provide normative discourses on the global skills, knowledge and attitudes that should be taught to equip young people to become 'change agents', this is yet to be reflected in educational policy in England. Central to addressing empirical gaps in research, is the exploration the impact of children's affective engagement in creative arts learning. Drawing from longitudinal action research as an artist–teacher–researcher in a primary school, the practice of Drama Worldbuilding is explored as a pedagogy of critical hope because it focuses on activating collective creativity and purposeful action. The research draws from theories of affect, wellbeing and immersive play to conceptualise new links between creativity, change making and wellbeing. The data analysis reveals a set of emerging creativity and wellbeing dispositions and adaptable competencies which support a deeper articulation of how creative pedagogy works through meta- affect. More widely, the research provides a heuristic approach which could be useful for teachers and artist educators interested in expanding their teaching repertoires, fostering students' collective creativity and critical thinking, offering a potential pedagogical space for rewilding the curriculum.